Controlling the pH and Temperature of Aquarium Water for Discus Fish Farming Based on ATMega328 Microcontroller with Internet of Things (IoT) System - Masthura Masthura; Abdul Halim Daulay; Dickiy Akbar (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2023)
Research that aims to produce and determine the performance of controlling the pH and temperature of aquarium water for discus fish cultivation based on the ATMega328 Microcontroller with the Internet of Things (IoT) system has been carried out. This system will only control the temperature and pH of the fresh water in the aquarium. The type of fish used in this study was Discus fish, with a standard living temperature of 28 – 30 °C and a pH of 5.5 – 7. The DS18B20 sensor was used as a temperature sensor, and the 4502C sensor was used as a water pH sensor. When the tool runs all components, the system can provide an excellent response to changes in temperature and pH of the water in the aquarium that are out of the expected range. This condition is indicated when the pH level of the aquarium water is out of range. Then, the system will turn on pumps one and two, which are turned off again if the pH level is within the range. If the water temperature is out of range, then the system will turn on the heater, which is then turned off and returned by the system if the water temperature is within the range. This condition is evidenced when testing the temperature sensor; the DS18B20 can read the temperature and pH conditions of 4502C water, can read acid and base levels in aquarium water, and then sends the results of the data reading to the internet-based Blynk application, which can provide an excellent response.